Meningkatkan kesopanan siswa terhadap guru melalui bimbingan konseling di sekolah SMAN 1 Rancaekek Bandung - Sartika, Dewi; Nurhalisyah, Elisa; Faturrohman, Fudhla Purnama (JURNAL BIMBINGAN KONSELING FLOBAMORA, 2025)
Politeness is considered important in social life, but it is often overlooked. Politeness in the school environment is very important in creating a comfortable and respectful learning environment. This research aims to provide insight into how guidance and counseling teachers can play a role in improving student politeness. In this study, we use a mix of research methods, namely qualitative research methods and quantitative research methods. This study results that the norms of good manners are formed from daily community interactions, but often students violate them due to the influence of promiscuity. It is important for the school and related parties to make politeness the main value in students' daily lives. The role of counseling guidance teachers is very important in accompanying students through a personal approach, but the limited time at school and the character of students who have been formed at home are the main obstacles. Therefore, synergy between teachers and parents is urgently needed to ensure that the value of politeness is applied consistently both at school and at home. This research concludes that with joint efforts, it is hoped that the values of politeness can be firmly embedded in students and make them individuals with noble character. This research contributes to providing a foundation for schools regarding the importance of improving student politeness through counseling guidance programs